1971
DOI: 10.1111/j.1476-5381.1971.tb07131.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of acetylcholine and carbachol on the chick biventer cervicis muscle

Abstract: Summary1. The possibility that carbachol may act on the chick biventer cervicis muscle by releasing acetylcholine was investigated. 2. Log dose-response curves for acetylcholine and carbachol were constructed in the presence of triethylcholine, tubocurarine and physostigmine, in both innervated and denervated chick biventer cervicis muscles. 3. The log dose-response curve for acetylcholine -was shallower than that for carbachol and was moved to the left by triethylcholine, indicating potentiation.In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, at ganglia, antibioticinduced depression of transmitter release would affect both responses to nerve stimulation and to added agonists. However, this cannot account for the observed depression of the responses to added agonists in the chick biventer cervicis muscle preparation as it has been shown that agonists act postjunctionally in this preparation (Marshall, 1971;Gandiha and Marshall, 1973).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, at ganglia, antibioticinduced depression of transmitter release would affect both responses to nerve stimulation and to added agonists. However, this cannot account for the observed depression of the responses to added agonists in the chick biventer cervicis muscle preparation as it has been shown that agonists act postjunctionally in this preparation (Marshall, 1971;Gandiha and Marshall, 1973).…”
Section: Discussionmentioning
confidence: 90%
“…progressively higher doses of quazodine enhanced responses to carbachol to a greater extent than responses to acetylchollne. This apparently greater potentiation of carbachol may be explained by the observation that in the chick biventer cervicis preparation the dose-response curve for carbachol is steeper than that for acetylcholine (Marshall, 1971). In fact when full dose-response lines were plotted from the results of seven further experiments, quazodine (200 ug/ml) caused parallel shifts of the log dose-response lines for acetylcholine and for carbachol corresponding to potentiation by 134 +0-12 and 1-41 + 0X08 fold respectively, and these factors are not significantly different.…”
Section: Effect Of Calciummentioning
confidence: 99%
“…in this muscle attains about 90% of that obtained by tetanic stimulation. Denervation of the chick biventer cervicis muscle was performed as described by Marshall (1971) under ether anaesthesia.…”
Section: Baby Chick Biventer Cervici8 Musclementioning
confidence: 99%